Analysis of Work Posture Using the Nordic Body Map (NBM) & Rapid Upper Limb Assessment (RULA) Method for Tofu Workers in Tahu Intan - Dewantari, Nustin Merdiana; Herlina, Lely; Wulandari, Anting; Ningsih, Nurhayati; Umyati, Ani (Universitas Sultan Ageng Tirtayasa, 2023)
Tofu is one food that has a lot of devotees, especially in Indonesia. Tahu Intan is a factory engaged in making tofu which is done traditionally and operates every day. During direct interviews with workers, workers complained of pain felt in the upper body so it needed further study. Awkward body postures can cause complaints which are often called Musculoskeletal disorders (MSDs). Therefore, the body postures of workers at Tahu Intan will be analyzed. By using the NBM and RULA questionnaires as an assessment of work posture, it is expected to be able to assess and provide recommendations for improvements for the Year of the Diamond. The assessment of the four workers for NBM was found to be in the moderate category, with the highest level of complaints in the upper left arm, right wrist, left and right hands, and pain in both knees, calves, ankles foot. The working posture that needs attention and improvement is in the process of boiling and filtering soybean juice